Have market policies turned Malawi’s large-scale farmers into subsistence maize producers? - Edelman, Brent; Mabiso, Athur; Nyirenda, Zephania; Kazembe, Cynthia (International Food Policy Research Institute, 2016)
In the last two decades, food security policy in Malawi has focused on enhancing the maize productivity of smallholder farmers, primarily through the Farm Input Subsidy Programme (FISP) (Chirwa and Dorward 2013). While this has raised maize yields, production shocks, such as droughts and floods, continue to result in wide-spread food insecurity in the country. In 2014/15, for example, a delayed onset of the rainy season, coupled with dry spells and flooding in different parts of the country, reduced maize production by about 30 percent (MoAIWD 2016), resulting in 2.8 million people requiring emergency food assistance (FEWSNET 2015). At the time of writing in mid-2016, the effects of El Niño were predicted to reduce maize production further. Government estimated maize production to be 2.4 million metric tons for the 2015/16 season, the lowest since FISP was introduced in 2005/06 (MoAIWD 2016). Even more Malawians are likely to be pushed into food insecurity.